2015
DOI: 10.1007/jhep07(2015)090
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions for extreme black hole magnetospheres

Abstract: We present new exact solutions of Force-Free Electrodynamics (FFE) in the Near-Horizon region of an Extremal Kerr black hole (NHEK) and offer a complete classification of the subset that form highest-weight representations of the spacetime's SL(2, R) × U(1) isometry group. For a natural choice of spacetime embedding of this isometry group, the SL(2, R) highestweight conditions lead to stationary solutions with non-trivial angular dependence, as well as axisymmetry when the U(1)-charge vanishes. In addition, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…Examining this limit using the approach of this paper could provide important feedback when comparing the analytical results with numerical simulations. The Stream equation for the near horizon geometry of ex-tremal Kerr magnetosphere, the so-called NHEK geometry, has received considerable attention in the literature [26][27][28][29] and it would be interesting to study the solutions found in the NHEK geometry using our small θ expansion. In fact, FFE exact solutions in the NHEK limit can be very important as starting points for a perturbative expansion around extremality in the same spirit as FFE exact solutions in a Schwarzschild background, such as the split-monopole, have been used as starting point for an expansion in small α, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining this limit using the approach of this paper could provide important feedback when comparing the analytical results with numerical simulations. The Stream equation for the near horizon geometry of ex-tremal Kerr magnetosphere, the so-called NHEK geometry, has received considerable attention in the literature [26][27][28][29] and it would be interesting to study the solutions found in the NHEK geometry using our small θ expansion. In fact, FFE exact solutions in the NHEK limit can be very important as starting points for a perturbative expansion around extremality in the same spirit as FFE exact solutions in a Schwarzschild background, such as the split-monopole, have been used as starting point for an expansion in small α, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To obey (27) we should thus ensure that c n,j = 0 for j = −2n, ..., −1 and that c n,0 is finite for r → ∞. The sufficient conditions for monopole-type asymptotics (19) are therefore c n,−2 = 0 , c n,−1 = 0 , d dr c n,0 = 0 for n ≥ 1 .…”
Section: A Angular Expansionmentioning
confidence: 99%
“…2014; Zhang et al. 2014; Lupsasca and Rodriguez 2015; Compère and Oliveri 2016; Gralla et al. 2016b).…”
Section: Scattering From Near-extremal Black Holesmentioning
confidence: 99%
“…for the electromagnetic fields (11) and (12) as they are approached. The condition can be obtained directly from the stream equation (15).…”
Section: The Stream Equationmentioning
confidence: 99%
“…On the other hand, in past years, exact solutions on extremely fast rotating black holes were obtained by focusing on the near-horizon region [10,11,12,13,14]. But, a smooth connection between these near-and far-region solutions is lacking.…”
Section: Introductionmentioning
confidence: 99%